2016
DOI: 10.1071/en15041
|View full text |Cite
|
Sign up to set email alerts
|

Are humans exposed to increasing amounts of unidentified organofluorine?

Abstract: Environmental context Polyfluorinated substances are anthropogenic chemicals that have been widely used in several industrial and commercial applications. Analysis of human plasma samples collected from Münster in Germany revealed, since the year 2000, increasing amounts and proportion of unidentified organofluorines. The increasing trend of unidentified organofluorines in plasma samples suggests that humans are being exposed to new and unidentified fluorinated products. Abstract Samples of human plasma (n=12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 42 publications
(7 reference statements)
0
92
1
Order By: Relevance
“…Overall these ndings corroborate observations in human plasma from Münster, Germany, which also showed an increasing proportion of unidentied organo-uorine in samples collected aer the year 2000. 7 We are unaware of any PFAS not included in the present work which display increasing time trends over the last decade in human serum; therefore, the cause of this increase in unidentied organouorine remains unclear at this time.…”
Section: Fluorine Mass Balancementioning
confidence: 93%
See 1 more Smart Citation
“…Overall these ndings corroborate observations in human plasma from Münster, Germany, which also showed an increasing proportion of unidentied organo-uorine in samples collected aer the year 2000. 7 We are unaware of any PFAS not included in the present work which display increasing time trends over the last decade in human serum; therefore, the cause of this increase in unidentied organouorine remains unclear at this time.…”
Section: Fluorine Mass Balancementioning
confidence: 93%
“…Moreover, recent organouorine mass balance experiments have reported large quantities of unidentied extractable organouorine (EOF) in human blood (15-67%) 5 and wildlife (68-90%). [5][6][7] Non-target analysis or suspect-screening (collectively referred to herein as 'NTA') workows offer the opportunity to elucidate novel PFAS which may account for unidentied organouorine in samples. The application of NTA workows within PFAS research have been reviewed recently.…”
Section: Introductionmentioning
confidence: 99%
“…By converting the identified organofluorine into F-concentration, using eq 1, a mass balance between the EOF and identified target PFAS can be calculated, giving the proportion of EOF that is known. This TOF method has been applied for surface water samples (Miyake et al, 2007a), aqueous film forming foams (Weiner et al, 2013), blood matrices (Miyake et al, 2007b, Yeung et al, 2008, Yeung and Mabury, 2016, marine mammal livers (Yeung et al, 2009b) and sewage sludge (Yeung et al, 2017).…”
Section: Figure 1: Examples Of Some Manufactured Organofluorine Substmentioning
confidence: 99%
“…Although most of the focus of PFASs research has been on perfluoroalkane sulfonic acids (PFSAs) and perfluoroalkyl carboxylic acids (PFCAs), two emerging groups of fluorinated phosphate surfactants, perfluoroalkyl phosphonic acids (PFPAs) and perfluoroalkyl phosphinic acids (PFPiAs) have recently attracted the attention of a number of researchers (D'eon et al 2009a;D'eon et al 2009b;Esparza et al 2011;Guo et al 2012;Loi et al 2013;Trier et al 2011;Yeung and Mabury. 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example PFPAs were detected in Canadian surface water and wastewater treatment plant effluents with concentrations ranging from 0.026 to 3.4 ng/L in surface water and 0.33 to 6.5 ng/L in wastewater (D'eon et al 2009), Perfluorooctyl phosphonic acid (C8-PFPA) was reported at a concentration of 1 ng/L in Dutch surface waters (Esparza et al 2011), and two PFPiAs congeners (C6/C6 and C6/C8) were detected in over 50% of U.S. human sera donors with the mean concentrations ranging from 4 to 38 ng/L (Lee and Mabury, 2011). PFPAs (C6, C8) and PFPiAs (C6/C6, C6/C8, C8/C8) have also been detected in German and Chinese human sera (Yeung and Mabury. 2016).…”
Section: Introductionmentioning
confidence: 99%